Medication Adherence, Quality of Life, and Rehospitalization in Post-Acute Coronary Syndrome Patients - Yustiana; Wenny Putri Nilamsari; Hendri Susilo; Dinda Monika Nusantara Ratri; Fatresye Mariati Bawole (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Post-ACS patients often face an increased likelihood of mortality, rehospitalization, and diminished quality of life as a consequence of poor medication adherence. Objective: This study aimed to evaluate the level of adherence to medication in post-ACS patients and its relationship with quality of life and rehospitalization rates. Methods: A cross-sectional, observational, single-center, prospective study conducted at Universitas Airlangga Teaching Hospital, Surabaya. Compliance with medication was evaluated using the Adherence Refill Medication Scale-7 (ARMS-7) questionnaire, while quality of life was measured using the Short Form-36 (SF-36) Quality of Life questionnaire. Rehospitalization rates were obtained through direct interviews and medical record observations within 45 days of hospital discharge. Results: In total, 39 patients participated in this study, with overall adherence rates of 35.89% for all prescribed medications, 53.85% for antiplatelets, 38.46% for statins, 55.56% for beta-blockers, and 58.06% for ACEIs/ARBs. Among the quality-of-life dimensions, social functioning had the highest score (93.01 ± 15.89), whereas physical role functioning had the lowest score (40.39 ± 35.18). Within 45 days of hospital discharge, 26% of the patients experienced rehospitalization. Statistical analysis indicated a positive correlation between adherence to all prescribed medications and physical role functioning in relation to QoL (p = 0.038). In addition, overall medication adherence was negatively correlated with the risk of rehospitalization (p = 0.019). Conclusion: Total medication adherence was associated with improved physical function and rehospitalization events. Providing education can lead to better therapeutic outcomes, improved quality of life, and reduced rehospitalization in patients.